Optimal proportional integral derivative controller for automatic voltage regulator system using particle swarm optimization algorithm - Wan Hassan, Wan Zakaria (2015)
Voltage control is very important in electrical power system to ensure safe operating condition for equipment. The purpose of this project is to investigate the application of Particle Swarm Optimization (PSO) algorithm in fine-tuning the Proportional, Integral and Derivative (PID) parameter of PID controller for Power System’s Automatic Voltage Regulator (AVR). AVR system is employed widely in exciter control system, mainly used in areas where the supply voltage is not stable and fluctuation of load occurs. The generator excitation system maintains generator terminal voltage and controls the reactive power flow using an AVR. A practical high order and linearized Power System AVR is modelled with four main components namely Amplifier, Exciter, Generator and Sensor. The proposed PSO algorithm had superior computational efficiency, stable convergence characteristic, and easy implementation. Fast tuning of optimum PID controller parameters yields high quality solution. To estimate the performance of optimal PID controller, a fitness function that use frequency-domain and time-domain were defined. A conventional technique, Ziegler-Nichols (ZN) tuning technique was used as the comparison for proposed algorithm. Simulation result shows that PID tuned by ZN technique improved the transient response of AVR but due to high order of AVR system, it is difficult to achieve optimal PID of AVR using ZN technique which is achievable using PSO algorithm.